Osiris [videorecording (DVD)] - Reichelt, Paul; Kaufman, William (Motion picture director); Martini, Max, 1969-; Hildebrand, Brianna, 1996-; Hamilton, Linda, 1956- (Vertical Entertainment, 2025)
Special Forces commandos are abducted mid-operation by a mysterious spacecraft and, upon awakening, team up with a mysterious woman in a fight for survival against a relentless alien race.